European Works Councils during the financial and economic crisis: Activation, stagnation or disintegration? - Valentina Mählmeyer; Luitpold Rampeltshammer; Markus Hertwig (European Journal of Industrial Relations, 2017)
The article compares changes in the European Works Councils (EWCs) at Ford and General Motors Europe during the financial and economic crisis. Previously, both were highly active and effective. Although both otherwise displayed quite different characteristics before the crisis, their reactions were quite similar. At both companies, competition and mistrust among representatives increased, resulting in a decline of integration and effectiveness. We explore the importance of personal relations as preconditions for stability and effectiveness in EWCs.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; automotive industry; European Works Councils; financial and economic crisis; Ford; General Motors; solidarity; transnational coordination